2007
DOI: 10.1152/ajpcell.00590.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel blocker of NFAT activation inhibits IL-6 production in human myometrial arteries and reduces vascular smooth muscle cell proliferation

Abstract: The calcineurin/nuclear factor of activated T cells (NFAT) signaling pathway has been found to play a role in regulating growth and differentiation in several cell types. However, the functional significance of NFAT in the vasculature is largely unclear. Here we show that NFATc1, NFATc3, and NFATc4 are expressed in human myometrial arteries. Confocal immunofluorescence and Western blot analysis revealed that endothelin-1 efficiently increases NFATc3 nuclear accumulation in native arteries. Endothelin-1 also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 41 publications
(40 reference statements)
8
94
0
Order By: Relevance
“…3D). These results are consistent with previous reports showing that ET-1 induces an increase in NFATc3 nuclear accumulation in vascular smooth muscle (25,48). Taken together, these results suggest that ET-1 may be an upstream mediator of H-IH-induced NFAT activation in aorta and mesenteric artery.…”
Section: H-ih Induces Hypertension In Micesupporting
confidence: 93%
See 1 more Smart Citation
“…3D). These results are consistent with previous reports showing that ET-1 induces an increase in NFATc3 nuclear accumulation in vascular smooth muscle (25,48). Taken together, these results suggest that ET-1 may be an upstream mediator of H-IH-induced NFAT activation in aorta and mesenteric artery.…”
Section: H-ih Induces Hypertension In Micesupporting
confidence: 93%
“…The number of NFATc3-positive nuclei was determined in aortic sections as previously described (11,20,27,47,48).…”
Section: Methodsmentioning
confidence: 99%
“…NFAT expression was found to be linked to the regulation of IL-6 expression, as it has been shown that application of NFAT inhibitors such as cyclosporin A resulted in a decrease of IL-6 expression. Likewise, overexpression of NFAT blockers caused a reduction in IL-6 mRNA (45). In addition, previous data Figure 5.…”
Section: Discussionsupporting
confidence: 61%
“…72 However, in the adult it is an important mediator of cardiac hypertrophy. 9,73 Wnt-5a-mediated non-canonical signaling has been reported to regulate human endothelial cell proliferation and migration.…”
Section: Canonical Wnt Pathwaymentioning
confidence: 99%